Necesario carácter vinculante de las recomendaciones efectuadas por la Contraloría General de la República y los órganos de control institucional en los servicios de control interno preventivos y simultáneos - Patron Bedoya, Pedro (2019)
The main focus of this article is to contribute to a more efficient, effective and transparent public management. For this, the author states that the recommendations made to public entities by the Comptroller General of the Republic and the Institutional Control Bodies, through internal control services, preventive and simultaneous, have vinculant character for the purpouse of strengthen in order to strengthen the National Control System, in the fight against corruption.